Cognitive Curiosity And Its Relation With Some Volleyball Skills For Students - Husni, Tahsein; Mahmood, Hydar; Alawi, Roaa (Journal of Physical Education, 2017)
Cognitive curiosity has a great effect on learning thus researchers used cognitive curiosity and its relation with the results of performing some skills in volleyball. The researcher aimed at identifying cognitive curiosity in forth year students as well as the level of artistic performance in volleyball and the relationship between artistic performance and cognitive curiosity in volleyball. The researcher used the descriptive method. The subjects were (50) forth year college students / university of Babel for the academic year 2016 – 2017. The researcher used cognitive curiosity scale designed by Maha Hadi Hussein that consists of 30 items about artistic performance in volleyball. The researchers concluded that there are significant correlations between cognitive curiosity and artistic skills performance in volleyball